Coping with uncertainty for parents of ill infants. - Erickson, Julie Reed. (The University of Arizona., 1988)
Uncertainty is recognized as a significant perceptual variable in the experience of illness. The purpose of this study was to gain an understanding of how parents of ill infants cope with the uncertainty inherent in illness-related events and situations. A conceptual framework of coping with uncertainty was proposed and tested. The four constructs in the model and their measures were perceived uncertainty (Mishel's Parents' Perceptions of Uncertainty Scale), cognitive appraisal (Lazarus and Folkman's Appraisal Questionnaire), coping efforts (Lazarus and Folkman's Ways of Coping Checklist) and cognitive schema (Mishel's Parents' Perceptions of Uncertainty Scale and grounded theory methodology). Methodological triangulation was used. A quantitative, longitudinal, descriptive correlational design examined the model. A qualitative study using grounded theory methodology explored the forming and using of a cognitive schema. A convenience sample of 37 parents of critically ill neonates participated in the quantitative study with 15 of those also participating in the qualitative study. Self report questionnaires measured model variables. Interviews comprised the grounded theory approach. Descriptive and correlational statistics characterized model variables and their relationships. Constant comparative analysis identified processes central to forming and using a cognitive schema. From the descriptive results, parents perceived high levels of uncertainty when measured at approximately 2.5 days following the ill infant's birth. Appraisal of uncertainty as harmful to well-bring was correlated with perceived ambiguity (r =.63) and complexity (r =.36). The coping efforts of self-blame (r =.53) and wishful thinking (r =.44) were related to the harm appraisal. Significant decreases in perceived ambiguity and lack of information were demonstrated when uncertainty was measured again at approximately eight days following birth. From the grounded theory methodology, three processes central to cognitive schema were identified (forming, framing, using) were discovered and conceptualized. When uncertainty was perceived, parents actively sought information in forming a schema. With sufficient information, information was categorized to frame an explanation of illness experiences. With framing, schema was created and used by the parents. Methodological triangulation accounted for consistencies and inconsistencies across quantitative and qualitative results. The model of coping with uncertainty was supported through triangulation.